CRITICAL PREPAREDNESS, READINESS AND RESPONSE TO COVID-19 PANDEMIC: A NARRATIVE REVIEW - Ravindra Pathirathna; Pamila Adikari; Dedunu Dias; Udara Gunathilake (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2020)
Background: The COVID-19 was declared as a pandemic by the World Health Organization (WHO). Globally, countries took actions to slow the spread and avoid overwhelming the health system. The WHO issued interim guidelines on critical preparedness, readiness and response actions against COVID-19 to assist level of preparedness and readiness.Aim: This study reviewed the work of Australia, Singapore, Sri Lanka and the United Kingdom on actions and priority areas of work as described in interim guidelines by the WHO in relation to the first two phases of disease transmission scenario.Methods: A non-systematic narrative review was conducted. Relevant documents available in selected websites were searched. The data generated were compiled, and information was synthesised within the WHO framework for critical preparedness, readiness and response actions against COVID-19. Further, scenarios of "no cases” and "sporadic cases” were analysed against the actions and priority areas of work of said framework.Results: Study revealed differences in implementation approach of strategic actions and priority areas of work, such as in terms of activation, timeliness of implementing emergency response plans, variations in case management strategies as seen in contact tracing, management of asymptomatic contacts, isolation, quarantine and selection of cohort for laboratory investigation. Besides, gaps were found in availability and activation of business continuity plans.Conclusion: Global political and health authorities need much robust mechanisms for preparedness, response and coordination of contagious diseases with similar nature. Even the occurrence of one case shall trigger stringent transmission prevention measures and initiate the actions and priority areas of work as stated in the WHO interim guideline.Keywords: pandemics, emergency response, health policy, COVID-19, emergency preparedness.